Do national cultures matter in the containment of COVID-19? - Cao, Cong; Li, Ning; Liu, Li (Emerald Group Holdings Ltd., 2020)
Purpose This paper empirically investigates how cultural variations in individualism and tightness affected the containment of COVID-19 using data from 54 nations during a 30-day period of government intervention. Design/methodology/approach The authors utilized the hierarchical regression approach to check the effects of three cultural variables – the individualism measure, taken from Hofstede’s six-dimension national culture index, and the measure of cultural tightness, based on the three tightness–looseness indexes calculated by Irem Uz (2015) and their interaction – on the changes in the prevalence rate (ΔPR) and crude mortality rate (ΔCMR) and case fatality rate (CFR) while controlling for the stringency of government responses to COVID-19, median age and population density. Findings Significant relationships were found between cultural variables and national performance in slowing the spread of the coronavirus, measured by ΔPR, ΔCMR and CFR. After controlling for the stringency of government responses, median age and population density, the authors found that cultural tightness and individualism as well as their interactions remain to be pivotal. Loose and individualistic cultures led to faster increases in PR and CMR and higher CFR. A four-quadrant conceptual framework is developed to categorize and discuss the national differences.